Peranan Kepala Sekolah dalam Meningkatkan Potensi Guru melalui Bimbingan Pembuatan Media Pembelajaran dari Limbah Anorganik di SDN Tinading - Saifullah Saifullah (Universitas Tadulako, 2021)
The principle of education in elementary schools is learning while playing so that the learning resources or media used for learning in students must refer to these principles. However, efforts to develop instructional media by teachers often face problems with funds. One way that can be done is by utilizing used or waste materials. On this account, this research aimed to increase the potential of teachers in developing instructional media. The method used in this research was the School Action Research (PTS) method with a qualitative approach. PTS is a research procedure adapted from Classroom Action Research (CAR). The research was conducted at SDN Tinading with the number of research subjects were 7 teachers. PTS was carried out in two cycles. The results showed that the provision of guidance can improve the ability of teachers in making recycled media from inorganic waste.